2014
DOI: 10.1016/j.forsciint.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Genuine and simulated suicide notes: An analysis of content

Abstract: The present study examined genuine and simulated suicide notes aiming to identify the measures of content that best differentiate between the two. Thirty-three genuine and thirty-three simulated suicide notes were content-analysed and data subjected to Smallest Space Analysis (SSA), a Multidimensional Scaling Procedure. The core of all suicide notes was discovered to be constructed with the use of three variables: expressions of love, positive construction of partner and apologies. Furthermore, four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 25 publications
4
37
1
Order By: Relevance
“…One way to examine this further would be to look at any of the writings of the offenders to link into their offenders narratives. Emerging research has shown the utility of examining notes and or written contact to build both victim and offender profiles (Ioannou & Debowska, ; Synnott, Coulias, & Ioannou, ; Synnott, Ioannou, Coyne, & Hemingway, ) The finding of the current study that the two groups do not form subgroups of serial killers regarding their spatial behaviour is not consistent with the findings of Salfati and Bateman (), in the sense that they found that sexual acts fell into the category of instrumental behaviours and stealing objects from the victim was found to be an expressive behaviour. However, the role of emotion and planning could not be investigated in this study and further research on the meaning of sexual and acquisitive offending behaviours for serial killers could clarify the role emotions play in the processes that influence location choices.…”
Section: Discussioncontrasting
confidence: 93%
“…One way to examine this further would be to look at any of the writings of the offenders to link into their offenders narratives. Emerging research has shown the utility of examining notes and or written contact to build both victim and offender profiles (Ioannou & Debowska, ; Synnott, Coulias, & Ioannou, ; Synnott, Ioannou, Coyne, & Hemingway, ) The finding of the current study that the two groups do not form subgroups of serial killers regarding their spatial behaviour is not consistent with the findings of Salfati and Bateman (), in the sense that they found that sexual acts fell into the category of instrumental behaviours and stealing objects from the victim was found to be an expressive behaviour. However, the role of emotion and planning could not be investigated in this study and further research on the meaning of sexual and acquisitive offending behaviours for serial killers could clarify the role emotions play in the processes that influence location choices.…”
Section: Discussioncontrasting
confidence: 93%
“…In accordance with the present results, the structural move apologizing to others was also found in previous studies of suicide notes (e.g., Chia et al, 2008;Delgado, 2013;Ioannou & Debowska, 2014;Jacobs, 1971;Prokofyeva, 2013) as were other structural moves identified in this analysis, including asking for forgiveness (e.g., Black & Lester, 2003;Chia et al, 2008;McClelland et al, 2000), saying goodbye (e.g., Darbonne, 1969;Ioannou & Debowska, 2014;Shapero, 2011), and assigning blame including self and others blame (e.g., McClelland et al, 2000;Nashef, 2010;Pestian et al, 2012;Sanger & Veach, 2008).…”
Section: Less Frequent Structural Moves In Suicide Notessupporting
confidence: 93%
“…A large and constantly growing body of literature has investigated suicide notes (e.g., Bauer et al, 1997;Black, 1993;Coster & Lester, 2013;Ioannou & Debowska, 2014;Joiner et al, 2002;Leenaars, 1988;O'Connor & Leenaars 2004;Shapero, 2011;, 1960. Suicide notes are texts usually written minutes before the suicide act (Leenaars, 1988;O'Connor & Leenaars, 2004), and they are considered as a source of data which researchers use to gain insights into the phenomenon of suicide.…”
Section: Background For the Studymentioning
confidence: 99%
See 2 more Smart Citations